2009
DOI: 10.1016/j.cognition.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Feelings of control: Contingency determines experience of action

Abstract: IntroductionThe evolution of human intelligence has allowed not just deeper understanding of the world, but a greater capacity to act on it. Such operant actions imply the ability to know that one is performing an action, and to represent its consequences (Dickinson & Balleine, 2000). Research on the epistemic content and conscious experience of action has identified two distinct processes underlying this ability.According to ideomotor theories (e.g. James, 1890), actions are internally represented by referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
147
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(161 citation statements)
references
References 17 publications
14
147
0
Order By: Relevance
“…However, considering Wenke and Haggard's (2009) design reveals that we have to be careful in interpreting their results. It is possible that the higher discrimination thresholds they found in causal trials simply reflect a transient, effector-specific modulation of the pacemaker induced by motor action.…”
Section: Empirical Evidence For Clock Slowing In Temporal Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, considering Wenke and Haggard's (2009) design reveals that we have to be careful in interpreting their results. It is possible that the higher discrimination thresholds they found in causal trials simply reflect a transient, effector-specific modulation of the pacemaker induced by motor action.…”
Section: Empirical Evidence For Clock Slowing In Temporal Bindingmentioning
confidence: 99%
“…Given that previous research has shown that temporal binding is rooted in causality (Buehner, 2015(Buehner, , 2012Moore, Lagnado, Deal, & Haggard, 2009), occurs across various stimulus modalities and tasks (Haering & Kiesel, 2014, 2015, and does not merely reflect processes related to motor preparation and execution, we focused our efforts on a simple causal versus non-causal interval distinction: In the experiments reported here, causal intervals were delineated by a participant's key press, which always caused a sensory outcome after a delay, while noncausal intervals were delineated by two sequential sensory outcomes. This manner of operationalizing causal and noncausal intervals presented the most efficient method of manipulating causality.…”
Section: Scopementioning
confidence: 99%
See 1 more Smart Citation
“…By computing contingency information, organisms are able to purposefully control their environment. Moore, Lagnado, Deal and Haggard (2009) investigated the relevance of contingency learning for intentional binding, by measuring its impact on the action component of intentional binding using the Libet clock method. They used the same probability manipulation as Moore and Haggard (2008) described above, with 75% and 50% outcome probability conditions.…”
Section: Causality and Intentional Bindingmentioning
confidence: 99%
“…Interestingly, both of these disorders have been linked to damage of the anterior insular cortex of the right hemisphere (Baier & Karnath, 2008;Karnath, Baier, & Nagele, 2005). However, it is important to note that this sense of agency may in fact have a significant postdictive or reconstructive component (Moore, Lagnado, Deal, & Haggard, 2009;Wegner, 2002) and thus is not necessarily an unambiguous index of intentionality. …”
mentioning
confidence: 99%